Currículo e literatura infantil amazonense: um diálogo intercultural no processo ensino-aprendizagem das crianças nos anos iniciais do ensino fundamental - Santos, Daniel Silva dos (Brasil, 2025)
This study aims to understand how the dialogue between knowledge from the official curriculum and cultural knowledge present in Amazonian children's literature can contribute to the teaching-learning process of children from the perspective of interculturality in a public school in Parintins, AM. The study also aims to verify which knowledge and/or knowledge make up the official curriculum of students in the second cycle of the research school and how they are worked on in classes in the different curricular components, as well as analyzing how Amazonian cultural knowledge can contribute to thinking in the construction of an intercultural curriculum as opposed to a hegemonic curriculum that recognizes the source of Amazonian knowledge. Qualitative in nature, it took place in a public school in the state network, whose subjects were two teachers. Data collection and production occurred through semi-structured interviews and document analysis. The data demonstrate that although local knowledge is present in the official curriculum, Amazonian literature is absent from school spaces and, consequently, from teaching practice. Hence the need to promote the use of this literature in schools in order to think about the curriculum from the perspective of interculturality.